Naringenin improves mitochondrial function and reduces cardiac damage following ischemia-reperfusion injury: the role of the AMPK-SIRT3 signaling pathway. Issue 5 (1st May 2019) - Yu, Li-Ming; Dong, Xue; Xue, Xiao-Dong; Zhang, Jian; Li, Zhi; Wu, Hong-Jiang; Yang, Zhong-Lu; Yang, Yang; Wang, Hui-Shan
Abstract : Naringenin directly inhibits mitochondrial oxidative stress damage and preserves mitochondrial biogenesis via AMPK-SIRT3 signaling, thus attenuating MI/R injury. Abstract : Mitochondrial dysfunction contributed greatly to myocardial ischemia-reperfusion (MI/R)-induced cardiomyocyte apoptosis. Naringenin is a flavonoid exhibiting potential protective effects on myocardial mitochondria under stress conditions. However, the detailed down-stream signaling pathway involved remains uncovered. This study was designed to elucidate naringenin's mitochondrial protective actions during MI/R with a focus on AMPK-SIRT3 signaling. Sprague-Dawley rats were administered with naringenin (50 mg kg −1 d −1 ) and subjected to MI/R surgery in the presence or absence of compound C (0.25 mg kg −1, Com.C, an AMPK inhibitor) co-treatment. An in vitro study was performed on H9c2 cardiomyoblasts subjected to simulated ischemia-reperfusion treatment. Before the treatment, the cells were administered with naringenin (80 μmol L −1 ) with or without SIRT3 siRNA/AMPK1α siRNA transfection. Naringenin improved post-reperfusion left ventricular systolic pressure and the instantaneous first derivative of left ventricular pressure, and reduced the infarction size and myocardial apoptosis index by suppressing mitochondrial oxidative stress damage (as evidenced by decreased mitochondrial cytochrome c release and oxidative markers) and enhancing mitochondrial biogenesis [as evidenced by increased NRF1, TFAM and oxidative phosphorylation subunit complexes (II, III and IV)]. These protective actions were abolished by Com.C ( in vivo ) or SIRT3 siRNA ( in vitro ) administration. Further investigation revealed that Com.C ( in vivo ) or AMPK1α siRNA ( in vitro ) markedly suppressed PGC-1α and SIRT3 levels while SIRT3 siRNA ( in vitro ) inhibited SIRT3 expression without significantly changing AMPK phosphorylation and PGC-1α levels. Taken together, we found that naringenin directly inhibits mitochondrial oxidative stress damage and preserves mitochondrial biogenesis, thus attenuating MI/R injury. Importantly, AMPK-SIRT3 signaling played a key role in this process.